PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DAN KINERJA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING DI RUMAH SAKIT ISLAM LUMAJANG - Wardani, Dian Kusuma; Cahyono, Dwi; Herlambang, Toni; Qomariah, Nurul (Jurnal Sains Manajemen dan Bisnis Indonesia, 2017)
ABSTRACTThis  study  aimed  to  examine  the  effect  of  leadership  style,  on  the commitment of the organization, and how dapak on job satisfaction and employee performance. Questionnaires were used to test the independent variables, the intervening  variables  and  the  dependent  variable  based  on  the  researcher compiled theoretical study. Statements in the questionnaire has proven its validity. Respondents are all employees of Islamic Hospital numbering as many as 125 employees. Questionnaires were distributed to respondents as many as 125 copies and all questionnaires were returned and filled in correctly so it is worth to be processed. The results of this study indicate that the first hypothesis is that there is a positive influence between the style of leadership of the Organizational Commitment.   Thus   the   leadership   style   variable   test   results   (X1)   on organizational commitment (Z) proved there is not significant positive effect between kulaitas service (X1) on organizational commitment (Z). In the second hypothesis shows that there is a positive influence between Organizational commitment and job satisfaction. Thus the test results variable organizational commitment (Z) to job satisfaction (Y1) proved no significant positive effect of organizational commitment (Z) to job satisfaction (Y1). While in the third hypothesis there is a positive relationship between leadership style on job satisfaction. Thus the results of testing leadership style variable (X) to job satisfaction (Y1) proved no significant positive effect of leadership style (X) to job satisfaction  (Y1).  Proof  fourth  hypothesis  indicates  that  there  is  a  positive influence between organizational commitment to employee performance. Thus the test results variable organizational commitment (Z) on the performance (Y2) proved positive influence is not significant organizational commitment (Z) on the performance (Y2). While in the fifth hypothesis that there is a positive influence among the leadership on employee performance. Thus the results of testing leadership style variable (X) on the performance (Y2) proved no significant positive influence leadership style (X) on the performance (Y2).Key  Words:  Leadership  Style,  Organizational  Commitment,  Job  Satisfaction, Employee Performance